Hollow carbon nanosphere embedded with ultrafine Fe3O4 nanoparticles as high performance Li-ion battery anode. (20th November 2016) - Liu, Lang; Zhang, Hua; Liu, Shuwu; Yao, Haimin; Hou, Haoqing; Chen, Shuiliang
Graphical abstract: Hollow carbon nanospheres embedded with ultrafine Fe3O4 nanoparticles (Fe3O4@HCNS) were synthesized by using carboxyl functionalized polystyrene latexes as template and polydopamine as carbon precursor for high performance Li-ion battery anode. Highlights: Hollow carbon nanospheres embedded with ultrafine Fe3 O4 nanoparticles (Fe3 O4 @HCNS) were synthesized. The Fe3 O4 @HCNS exhibited high reversible capacity, excellent cycling stability and high-rate capability. The ultrafine Fe3 O4 NPs ensured small volume change and shorten the path of Li ions intercalation. The mesoporous HCNS alleviated the volume change and protected the ultrafine Fe3 O4 NPs from aggregation. Abstract: Hollow carbon nanospheres embedded with ultrafine Fe3 O4 nanoparticles (Fe3 O4 @HCNS) were synthesized by using carboxyl functionalized polystyrene latexes as template and poly dopamine as carbon precursor. The ultrafine Fe3 O4 nanoparticles (NPs) had a small size of 3 ∼ 5 nm and the HCNS had a thin shell thickness of 15 nm in the Fe3 O4 @HCNS. As a promising anode material for lithium-ion batteries, the Fe3 O4 @HCNS exhibited high reversible capacity, excellent cycling stability (1380 mA h g −1 after 200 cycles at 1 A g −1 ) and high-rate capability (475 mA h g −1 at 5 A g −1, 290 mA h g −1 at 10 A g −1 ). The outstanding performance was attributed to the unique structure of the Fe3 O4 @HCNS, which greatly shorten the path of Li ions intercalation during charging and discharging.